Effects of ginsenoside Rg1 on HIF-1a, VEGF, and ET-1 expression in mice with chronic intermittent hypoxia and pain - QIN, Fei; WANG, Peng; ZHANG, Min; QIANGZE, Zhang; HE, Zhuang; LIU, Bing (Food Science and Technology, 2024)
Chronic intermittent hypoxia (CIH) is associated with pulmonary hypertension and lacks effective early intervention approaches. Our study intends to investigate the protective effect of ginsenoside Rg1 on pulmonary small artery damage of CIH in mice. A total of 72 SPF-grade male C57BL/6 mice were randomly divided into an experimental group, which received ginsenoside Rg1 10 mg/kg (low-dose group, group T1) and 20 mg/kg (high-dose group, group T2) daily, and the control group (group C), which received an equal volume of normal saline every day. Samples were collected on days 7, 10, and 14 after treatment to assess HIF-1a, VEGF, and ET-1 levels by immunohistochemical staining, serum level of HIF-1a, VEGF, and ET-1 by ELISA, or the mRNA level of HIF-1a, VEGF, and ET-1 by real-time PCR. The control group presented increased serum levels of HIF-1a, VEGF, and ET-1 from days 7 to 14. Compared with the control group, the treatment group showed significantly decreased serum levels of HIF-1a, VEGF, and ET-1 on day 7, 10, or 14 at the same time points (P < 0.05). Consistently, immunohistochemical staining analysis also showed an increased trend of HIF-1a, VEGF, and ET-1 IOD values in the control group, which were all decreased in the treatment group at the same time points with the lower level in the T2 group than the T1 group (P < 0.05). Moreover, HIF-1a, VEGF, and ET-1 mRNA levels in groups C, T1, and T2 also showed similar results to immunohistochemical staining (P < 0.05 or P < 0.001). In the treatment group, HIF-1a was positively correlated with VEGF or ET-1 and VEGF was positively correlated with ET-1. Ginsenoside Rg1 inhibits the expression of HIF-1a, VEGF, and ET-1 in mice with CIH and pain.